A model of ethical management in organisations: an analysis of al-Ghazali's theory of management - Mohd Hidayat Mahadi,; Mohd Haidhar Kamarzaman,; Mohd Asyran Safwan,; Muhammad Hilmi Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ethical management is a crucial component of any organisation. While Western scholars have extensively explored the theory of ethical management in organisations, there have been limited contributions from Islamic scholars, serving as a major guideline. This article aims to shed light on al-Ghazali’s perspective on organisational management theory. According to al Ghazali, ethical management within an organisation entails a fundamental principle: placing the concept of Tawhid at the forefront. This means ensuring that the organisation's actions and decisions are aligned with the unity and oneness of God. Next, the organisation should focus on implementing the four main aspects of management: planning (al-Takhtit), organisation (al-Tanzim), supervision (al-Wiqayah) and leadership (al-Qiyadah). Incorporating these practices can significantly impact the overall culture of the organisation, promoting an ethical and harmonious environment by making religion as the foundation.